Implementasi K-Means Clusstering Dalam Pengelompokkan Produksi Daging Ayam Menurut Provinsi Di Indonesia - sahri, aulia eka (Jurnal PROCESSOR, 2023)
Chicken meat is a food ingredient with balanced nutrition needed by the body. The quality of each meat is a combination and variation of the properties of the meat, so that meat products can be eaten. The purpose of this study was to classify chicken meat production by province in Indonesia using K-Means Clustering analysis. From the analysis results, the best Average Silhouette Total is 0.84 and consists of 3 clusters. Cluster 1 is a province group with high chicken meat production, with a total of 19 provinces. Cluster 2 is a province group with moderate chicken meat production, with a total of 4 provinces. Cluster 3 is a province group with low chicken meat production, with a total of 11 provinces.